Speleothems as Magnetic Archives: Paleosecular Variation and a Relative Paleointensity Record From a Portuguese Speleothem - J. M. Ponte; E. Font; C. Veiga‐Pires; C. Hillaire‐Marcel (Geochemistry, Geophysics, Geosystems, 2018)
Abstract We provide a high‐resolution and complete paleomagnetic study from a middle‐Holocene (~4,100–3,300 years Before Common Era, BCE) dome‐shaped speleothem (SPAIV) from Algarve, Portugal. Our results show that the SPAIV speleothem carries a primary and stable remanent magnetization, for which directions are similar to other speleothems from the western Alps. Magnetic declination and inclination curves are also comparable to current paleosecular variation models (SHA.DIF.14k, CALS10k.1b, and pfm9k.1a), one of them (SHA.DIF.14k) fitting better with the present data set. Relative paleointensity was estimated using two different methods: conventional normalization of natural remanent magnetization by anhysteretic and isothermal, and the pseudo‐Thellier method, which is being tested here for the first time in a speleothem. Both methods show similar results, with a minimum intensity peak at ~3,850 years BCE. This low relative intensity is observed in all samples pertaining to the same respective calcite laminae. These results suggest that high growth rate speleothems are good high‐resolution recorders of the direction and intensity of the Earth's magnetic field.